A pharmacological approach towards mechanisms Of chronic stress inducing neuroinflammation, Depression and cognitive impairment. - BODDU V S CHANDRASEKHAR; ELANGO P; D RAJUKUMAR; S.UMA MAHESWARI (International Journal of Pharma and Bio Sciences, 2017)
Stress is a major contributor factor inducing depression and cognitive impairment. Up-to-date treatment is inefficient for depression with cognitive impairment due to poorly understood patho-physiological changes in chronic patients of stress. In this review, we present data of possible mechanism involved in chronic stress induced neuro behavioural changes like depressive, anxiety and memory impairment. Chronic stress increase levels of glucocorticoids, glutamate, and also evokes the pro inflammatory mediators such as interleukin 1 beta (IL-1 β), interleukin-6(IL-6), tumour necrosis factor α (TNF-α). These changes alter neurotransmitter levels and atrophy of dendrites CA1 and CA3 neurons in hippocampus causes like anxiety, depression and cognitive impairment. This article provides possible mechanism to novel pharmacological target for stress induced neuro inflammation, depression and cognitive impairment.